Synergistic reinforcement of glass-ionomer dental cements with silanized glass fibres. (6th June 2020) - Salehi, Ghazaleh; Behnamghader, Aliasghar; Pazouki, Mohammad; Houshmand, Behzad; Mozafari, Masoud
ABSTRACT: The purpose of this study is to evaluate the general function and properties of a new class of reinforced glass-ionomer cements (GICs). In this regard, GIC powders based on a molar composition of 4.5SiO2.3Al2O3.1.5P2O5.3CaO.2CaF2 were synthesised via a melt-quenching method. The cement reinforced with silanized fibers (CSFs) were made by adding silanized E-glass fibers to the glass powder, before mixing with FUJI II LC, and then cured. The CSFs achieved maximum values of mechanical properties and showed a lower increase in roughness value compare to the other tested groups. Additionally, the CSFs demonstrated acceptable biocompatibility to fibroblast cells. Reinforcing the GICs with silanized glass fibers could improve the mechanical properties and toughening behavior of the final products, making them a promising biomaterial for dental restorative applications.